저장 방법과 기간에 따른 거머리말 (Zostera marina)의 발아율 - 박정임; 박재희; 이근섭; 손민호; Park, Jung-Im; Park, Jay Hee; Lee, Kun-Seop; Son, Min Ho (Pada (Hanʼguk Haeyang Hakhoe), 2014)
To determine the optimal storage method and longest possible storage period of Zostera marina seeds, we examined post-storage germination rates using different storage methods and periods for Z. marina seeds harvested in southern coast of Korea. Storage methods included in seawater at room temperature with air supply, seawater at $4^{°}C$, seawater at $30^{°}C$, an aquarium with continuous seawater circulation, seawater at room temperature in an airtight tank, a refrigerator at $-20^{°}C$, and a desiccator at room temperature. Germination rates of Z. marina seeds stored in seawater at $4^{°}C$ showed highest germination (52.0%), whereas those of seeds stored in seawater at room temperature and an aquarium were 27.4% and 17.7%, respectively. But the seeds stored in seawater at $30^{°}C$, a refrigerator, and a desiccator did not germinate. Storage periods were 10, 20, 30, 60, 180 and 240 days of storage. Z. marina seeds maintained germination rates of 46.4~52.4% until 10~60 days of storage, but showed rapidly decreasing germination rates after then and no germination after 240 days. 거머리말 종자의 적절한 저장 방법과 저장 가능한 기간을 알아보기 위하여 우리나라 남해안에서 채취한 거머리말 종자를 이용하여 다양한 저장 방법과 저장 기간 후 발아율을 조사하였다. 거머리말 종자의 저장 방법은 공기가 공급되는 실온의 해수, $4^{°}C$의 해수, $30^{°}C$의 해수, 해수가 공급되는 수조, 밀폐된 해수, 냉동, 건조의 방법으로 저장하였다. $4^{°}C$의 해수에 저장한 거머리말 종자의 발아율이 가장 높았으며(52.0%), 해수가 유입되는 수조와 실온에서 저장한 종자의 발아율은 각각 17.7%와 27.4%가 나타난 반면, 건조, 냉동한 종자와 $30^{°}C$의 해수에 보관한 종자는 전혀 발아하지 않았다. 거머리말 종자의 각 저장 기간은 10, 20, 30, 60, 180일과 240일 동안 저장하였다. 10~60일 동안 저장한 거머리말 종자는 46.4~52.4%의 발아율을 유지하였으나, 저장 기간이 길어질수록 급격히 발아율이 감소하여, 240일 저장한 거머리말은 전혀 발아되지 않았다.